Improving Prospective Memory Performance in Community-dwelling Older Adults: Goal Management Training and Implementation Intentions. Issue 5 (20th October 2021) - Fine, Lara; Loft, Shayne; Bucks, Romola S.; Parker, Denise; Laws, Manuela; Olaithe, Michelle; Pushpanathan, Maria; Rainey Smith, Stephanie R.; Sohrabi, Hamid R.; Martins, Ralph N.; Weinborn, Michael
ABSTRACT: Aim: The present study tested a compensatory executive intervention for prospective memory (goal management training) for the first time in older adults. Prospective memory (the ability to remember and execute a task in the future) declines with age, with significant implications for older adults' activities of daily living and quality of life. Prospective memory interventions have focused primarily on the retrospective component of prospective memory (e.g., implementation intentions). However, executive dysfunction is also implicated in age-related prospective memory decline. Methods: Community-dwelling older adults were randomly allocated to receive goal management training, implementation intentions or no intervention. Prospective memory was assessed before and after the intervention with a well-validated laboratory-based prospective memory measure.  Results: Contrary to predictions, neither goal management training nor implementation intentions were successful at improving prospective memory in healthy older adults. Participants who received goal management training were more likely to have difficulty comprehending the intervention. Post-hoc analyses suggested implementation intentions improved prospective memory specifically for participants with poorer baseline prospective memory.  Conclusions: These results represent important cautionary findings about the possible limitations of goal management training to improve prospective memory in older adults. Future research should also consider the role of baseline prospective memory ability in affecting response to compensatory intervention.